CSS3 pushing the limits - Greig, Stephen (Pushing the Limits., 2013)
"Representing an evolutionary leap forward for CSS, CSS3 is chock-full of new capabilities that dramatically expand the boundaries of what a styling language can do. But many of those new features remain undocumented, making it difficult to learn what they are and how to use them to create the sophisticated sites and web apps clients demand and users have grown to expect."--Publisher website.